Hierarchically structured reactors containing nanocarbons for intensification of chemical reactions. Issue 43 (18th October 2017) - García-Bordejé, Enrique; Liu, Yuefeng; Su, Dang Sheng; Pham-Huu, Cuong
Abstract : This review reports on the recent developments in hierarchically structured catalyst systems based on self-supported nanocarbons and homogeneous decoration of a macroscopic host matrix with a layer of carbon nanotubes (CNTs) or carbon nanofibers (CNFs). Abstract : Carbon nanomaterials, such as carbon nanotubes, carbon nanofibers and graphene, featuring functional properties and tailored nanoscale dimensions have been widely used in different research fields, especially for catalysis and sustainable chemistry. Hierarchically structured reactors, combining nanoscopic coating carbon layers to disperse the active phase or even directly as metal-free catalysts, with controlled macroscopic shapes, have been extensively developed over the last few decades for numerous relevant catalytic processes, where mass and heat transfer is easily optimized for better catalytic performance and stability. The 3D structuration enables the full exploitation of the intrinsic activity of the catalyst and its industrial deployment without drawbacks linked with nanomaterials. In this review article, we will summarize the recent developments involved in the field of hierarchically structured reactors, i.e. monoliths, foam and other materials, containing carbon nanomaterials. It is expected that such structured reactors will receive high scientific and industrial interest in the future not only in the field of catalysis but also in those linked with wastewater purification or aerosol filtration processes. It will also be evidenced how hierarchically structured materials have contributed to the intensification of catalytic processes compared to conventional reactors, thus paving the way to the enhancement of other chemical reactions and their industrial deployment.